Outcome analysis of single-stage transanal endorectal pull through in selected patients with hirschsprung disease - Suraj Gandhi; Apoorva Makan; Neha S Shenoy; Syamantak Basu; Akriti Tulsian; Hemanshi Shah (Wolters Kluwer Medknow Publications, 2022)
Background: Hirschsprung disease is a notable cause of neonatal intestinal obstruction and constipation in older children. Transanal endorectal pull through (TEPT) is a newer technique of definitive management as against staged procedures. The aim of our study is to evaluate the feasibility and outcome of the procedure in selected children with Hirschsprung disease managed by this technique with review of the literature. Materials and Methods: Medical records of 12 children who underwent single-stage TEPT in a tertiary care centre over a period of 3 years from 2015 to 2018 were reviewed and retrospectively analysed on the basis of age, investigations, intraoperative parameters, complications, functional outcome and hospital stay. Results: The median age at surgery was 9 months. Nine patients were boys. The median weight of patients was 7.5 kg. The transition zone was observed at the level of the rectosigmoid in eight patients (66.6%) and sigmoid colon in four patients (33.3%). The mean length of muscle cuff was 3 cm, the mean length of resected bowel was 25 cm, the median operative time was 105 min and the mean hospital stay was 8 days. Perianal excoriation (n = 2) and enterocolitis (n = 1) were complications encountered postoperatively; however, no patient had cuff abscess, anastomotic leak or stricture. Stool frequency initially at 2 weeks was average of six to ten times a day, which gradually reduced to two to three times a day by 3 months postoperatively. None of the patients had faecal soiling or constipation on follow-up. Conclusion: Single-stage transanal endorectal pull through is an effective technique in the management of Hirschsprung disease with minimal complications.